A rapid multi-device wireless power transfer scheme using an intermediate energy storage. Issue 4 (2nd April 2016) - Yoon, C.S.; Nam, S.S.; Cho, S.H.
Abstract : We introduce a new time-division multiplex wireless power transfer (TDM-WPT) scheme for charging multiple devices with a single transmitter. More specifically, our proposed scheme adopts the intermediate energy storage (IES) circuit which enables storing the received energy from the source temporarily and then supplying it to the load. Thus, by adopting the IES, the receiver can charge the battery with the stored energy in the IES even while the receiver is not performing the direct charging process (from the transmitter). This allows charging multiple receivers simultaneously in a virtual manner, and it eventually leads to the reduction of overall charging time. For the theoretical verification, we analyse the performance of our proposed scheme based on the identical environment and in some selected results. We show that with our proposed scheme the required total charging time can be reduced compared to the conventional TDM-WPT. We also consider practical load (battery charger) requirements which change continuously. We present the simple guidelines for some key design parameters such as the optimal capacity of the IES and the proper number of receivers. Note that we additionally present the sample IES circuit and the related circuit simulation to show the detailed operation and the feasibility of the proposed scheme.